Os conceitos de risco e vulnerabilidade social na política de assistência social: tendências do debate teórico crítico do serviço social - Santos, Ana Paula do Nascimento (2023)
This work has as its object of study the ideological conceptions of risk and social vulnerability. The central objective was to analyze the critical production of Social Work on the implications of the concepts of risk and social vulnerability in the field of Social Assistance. To achieve the central objective, we seek to understand the foundations of social-liberal ideology and the concepts of social risk and social vulnerability, understand Social Assistance in Brazil and the implications of the social-liberal prescription in its current configuration, as well as systematize the criticism that the Social Service has been working on the incorporation of the concepts of risk and vulnerability in the field of Social Assistance. This is an exploratory research, of a qualitative nature, developed through bibliographical research analyzing the “state of the art” of academic productions relating to the object of study. The main sources are theses and dissertations available in the Brazilian Digital Library of Theses and Dissertations (BDTD) for the last ten years (2012-2022). The data were analyzed in light of the historical-dialectical materialist approach method, as it is understood that it allows the apprehension of reality based on the category of totality, characterizing it in a historical-critical way. The analysis of Social Service literature shows that it is common for all researchers to understand that the National Social Assistance Policy is a great achievement in the field of social policies, however, the contradictions that challenge its perspective as a social right in a context of structural capital crisis. In this way, the influence of authors aligned with the theoretical precepts adopted by international organizations and social-liberal ideology results in harmful consequences for Social Assistance, as it now has the character of social risk management. It is possible to point out that the concepts of risk and social vulnerability were incorporated into the regulatory framework of Brazilian social assistance policy, in an ideological perspective that hides and veils the determinations of poverty and social inequalities, thus demanding, on the part of Social Service, a consistent theoretical debate that guides the political dispute of Social Assistance in line with the Ethical-Political Project of the Profession.